Threshold of phenylacetylglutamine changes: exponential growth between age and gut microbiota in stroke patients - Liu, Yang; Chu, Min; Wang, Delong; Li, Qian; Lin, Jixian; Zhao, Jing (Frontiers in Neurology, 2025)
Importancephenylacetylglutamine (PAGln), a gut microbiota-derived metabolite, is linked to increased platelet reactivity and thrombosis risk. However, its relationship with age, particularly the non-linear patterns in ischemic stroke patients, remains unclear.ObjectivesTo explore the non-linear relationship between age and plasma PAGln levels in ischemic stroke patients, focusing on identifying exponential growth trends and critical age thresholds.Design, setting, and participantsThis single-center, prospective cohort study was conducted at the Department of Neurology, Minhang Hospital, Fudan University, from January 2022 to December 2023. A total of 121 patients with ischemic stroke were consecutively enrolled. Demographic information, lifestyle factors, stroke characteristics, and comorbidities were systematically collected. Plasma PAGln levels were measured using rapid resolution liquid chromatography–quadrupole time-of-flight mass spectrometry. Generalized additive models and smoothing curve fitting were applied to assess non-linear relationships between age and PAGln levels, with threshold effect analysis used to identify age breakpoints. Multivariable regression models were applied to adjust for confounders, and subgroup analyses tested the robustness of findings.Main outcomes and measuresPlasma PAGln levels and their association with age in ischemic stroke patients, evaluated through non-linear models and regression analysis.ResultsSignificant differences in PAGln levels were found across age quartiles (P = 0.004), rising from 186.87 ± 95.49 μmol/L in the youngest quartile (35–54 years) to 433.11 ± 474.03 μmol/L in the oldest quartile (69–87 years). A non-linear association between age and PAGln levels was identified (P = 0.0006). Smoothing curve fitting revealed an exponential increase in PAGln levels with age. A threshold effect analysis pinpointed a breakpoint at 71 years. Below this age, no significant association between age and PAGln was observed (P = 0.5394), while above 71, a significant exponential increase in PAGln levels was detected (P < 0.0001). Subgroup analyses confirmed consistent results across various patient characteristics, with no significant interactions.Conclusions and relevanceA non-linear exponential relationship exists between age and plasma PAGln levels in ischemic stroke patients, with a marked increase after 71 years. Elevated PAGln levels in elderly patients suggest significant metabolic dysregulation, potentially raising thrombosis risk. Monitoring PAGln levels in stroke patients over 71 years could provide valuable insights for personalized interventions to reduce thrombotic complications.